2020
DOI: 10.1007/s11365-020-00689-4
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship of an institutional field: the emergence of coworking spaces for digital business models

Abstract: Coworking spaces have been proliferating world-wide in urban and rural areas while facilitating entrepreneurship and new, especially digital business models. Our research analyzes the worldwide expansion by drawing upon mechanisms from institutional theory. We argue that the sense of community, emotional activation, the local communities together with the digital linkages and the open office allowed coworking spaces to evolve as a real space for entrepreneurship. The common lifestyle and the high digital ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 79 publications
2
47
0
17
Order By: Relevance
“…For companies, social interaction in this context is a linchpin, especially for intrapreneurial behavior (Gerards et al 2020 ). CWS (social) interaction adds value simply by being present and opening talking-restraints of involved parties, eventually increasing entrepreneurial outcomes (Bouncken et al 2020a , b ; Jeske and Ruwe 2019 ). Overall, Jeske and Ruwe ( 2019 : 174) emphasize that CWS “provide important sources of support, learning and networking opportunities”.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…For companies, social interaction in this context is a linchpin, especially for intrapreneurial behavior (Gerards et al 2020 ). CWS (social) interaction adds value simply by being present and opening talking-restraints of involved parties, eventually increasing entrepreneurial outcomes (Bouncken et al 2020a , b ; Jeske and Ruwe 2019 ). Overall, Jeske and Ruwe ( 2019 : 174) emphasize that CWS “provide important sources of support, learning and networking opportunities”.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Overall, Jeske and Ruwe ( 2019 : 174) emphasize that CWS “provide important sources of support, learning and networking opportunities”. Bouncken et al ( 2020a : 1465) highlight the closeness to the entrepreneurship field and describe a CWS as “a real space for entrepreneurship”.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Although many hybrids between coworking spaces and other business centre concepts are increasingly present, Waters-Lynch et al ( 2016 ) point out differences from other shared office concepts in the aesthetic design of coworking spaces. Weijs-Perrée et al ( 2016 ) also showed a clear difference with serviced offices, which are all located in modern office spaces, while coworking spaces can also be located in former industrial era warehouses or factories (Deskmag 2016 ) and are thus more diverse in outside and inside appearance (Bouncken et al 2020b ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Apart from the literature that explicitly addresses institutional entrepreneurship, another body of literature can be identified that deals with both institutions and entrepreneurship but does not explicitly refer to institutional entrepreneurship theory. Especially, this research stream not directly related to institutional entrepreneurship examines the favoring or inhibiting effects of existing institutions on entrepreneurial behavior (Bouncken et al 2020;Pacut 2020;Sobel 2008;Wang et al 2019;Welter and Smallbone 2011) and, more generally, on the emergence, flourishing, and success of entrepreneurship (Acs et al 2018;Aidis et al 2008;Ali et al 2020;Bouncken et al, 2020;Bowen and Clercq 2008;Dai and Si 2018;Eijdenberg et al 2019;Estrada-Robles et al 2018;Estrin et al 2013;Lv et al 2020;Galindo-Martín et al 2019;Manolova et al 2008;Queirós et al 2019;Urbano et al 2020), especially where institutional voids exist (Puffer et al 2010). Rather than institutional entrepreneurship's focus on institutional change, this body of research sees entrepreneurs as embedded in existing institutions.…”
Section: Performance Analysesmentioning
confidence: 99%